Developing English E-Module for Culinary Students at Bali Crystal College - I Wayan Wira Praditya; I Gede Budasi; Dewa Putu Ramendra (IDEAS: Journal on English Language Teaching and Learning, Linguistics and Literature, 2026)
Preliminary observations show that there is no standardized English for Specific Purposes (ESP) teaching materials for culinary students at LPK Bali Crystal College. This research aims to identify the English learning needs of culinary students, develop English for Culinary e-modules based on these needs and SKKNI, and assess the quality of the e-modules developed. This study uses a Research and Development (R&D) approach with an adaptation of the Borg and Gall (2003) model which includes the exploration, development, and validation stages, and refers to the principles of ESP material development from Hutchinson and Waters (1987). Data were collected through document analysis, interviews, and questionnaires involving 30 culinary students and 2 instructors, then analyzed qualitatively using Miles and Huberman (1994) and quantitatively with descriptive statistics according to Gravetter and Wallnau (2016). The results of the needs analysis show that students need authentic, contextual material with the world of culinary work, integrated with four language skills, interactive, and covering 12 topics of language functions relevant to professional kitchen activities. Based on these findings, an e-module was developed consisting of 12 chapters and equipped with text, images, audio, and video. The validation results showed that the quality of the media with a mean of 4.90 and 4.80 and the quality of the content with a mean of 4.88 and 4.94, all of which were in the very good category. Thus, the e-module developed is declared suitable for use as ESP teaching materials for culinary students at LPK Bali Crystal College.